Chemoprevention of Head and Neck Cancer by Green Tea Extract: EGCG—The Role of EGFR Signaling and "Lipid Raft". (27th December 2010) - Masuda, Muneyuki; Wakasaki, Takahiro; Toh, Satoshi; Shimizu, Masahito; Adachi, Seiji
Abstract : Over the past decade dose-intensified chemo-radiotherapy or molecular targeted therapy has been introduced into the treatments of head and neck squamous cell carcinoma (HNSCC) to improve the outcomes of this dismal disease. However, these strategies have revealed only limited efficacy so far. Moreover, the frequent occurrences of second primary tumor further worsen the prognosis of patients. In this context, early detection and chemoprevention appear to be a realistic and effective method to improve the prognosis as well as quality of life in patients with HNSCC. In this short paper, we discuss the potential of green tea extract, (-)-epigallocatechin-3-galate (EGCG) in HNSCC chemoprevention, focusing on two aspects that are provided recently: (1) evidence of clinical efficacy and (2) unique biological effects on "lipid raft" that emerged as an important platform of numerous biophysical functions, for example, receptor tyrosin kinases (RTKs) signalings including epidermal growth factor receptor (EGFR), which play critical roles in HNSCC carcinogenesis.